2003
DOI: 10.1046/j.1360-2276.2003.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

CTLA‐4 positive T cells in contrast to procalcitonin plasma levels discriminate between severe and uncomplicated Plasmodium falciparum malaria in Ghanaian children

Abstract: Summary Procalcitonin (PCT) plasma levels and the fraction of CTLA‐4‐positive T cells are both elevated in acute Plasmodium falciparum malaria in human adults and the degree of elevation is positively correlated with other markers of disease severity, for example with parasitaemia. However, the clinical manifestations of malaria are strongly age‐dependent and children from endemic areas carry the main disease burden. Therefore, we measured PCT plasma levels and CTLA‐4 expression by T cells in four groups of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
6
27
0
Order By: Relevance
“…Initiation of antiplasmodial treatment reduced CTLA-4 expression to background levels within a few days [41]. Braun et al reported that CTLA-4 expression by T cells from Ghanaian children was induced exclusively during severe malaria [42]. This finding supports the hypothesis that strong T cell activation as measured by CTLA-4 expression is not only the by-product of a high parasitemia, but contributes directly to the pathogenesis of P. falciparum malaria.…”
Section: Ctla-4/b7 Interactions In Parasitic Infec-tionssupporting
confidence: 66%
See 1 more Smart Citation
“…Initiation of antiplasmodial treatment reduced CTLA-4 expression to background levels within a few days [41]. Braun et al reported that CTLA-4 expression by T cells from Ghanaian children was induced exclusively during severe malaria [42]. This finding supports the hypothesis that strong T cell activation as measured by CTLA-4 expression is not only the by-product of a high parasitemia, but contributes directly to the pathogenesis of P. falciparum malaria.…”
Section: Ctla-4/b7 Interactions In Parasitic Infec-tionssupporting
confidence: 66%
“…suppression of T effector functions during leishmaniasis by CD4 + CD25 + CTLA-4 + regulatory T cells [34][35][36] positive correlation between CTLA-4 expression by CD4 + T cells and disease severity in human malaria [41,42] increased incidence of cerebral malaria during P. berghei ANKA (PbA) infection of mice upon CTLA-4 blockade [43] IL-12-and IFN--dependent liver pathology during PbA infection upon CTLA-4 blockade [44] reduced peak parasitemia and earlier parasite clearance in murine P. yoelii NL infection upon CTLA-4 blockade [45] Plasmodium ssp.…”
Section: Btla/hvem and Light/hvem Interactions In Parasitic Infectionsmentioning
confidence: 98%
“…Although the range is wide, values as high as 662 ng/mL have been reported (126). Although some authors note a significant positive correlation with severity (126,127), others find no correlation (128). Levels decrease with therapy (127,129).…”
Section: Sepsismentioning
confidence: 93%
“…CTLA-4 is involved in the regulation of T-cells and is up-regulated during the T-cell-mediated immune response. CTLA-4-positive cells are elevated in acute P. falciparum and vivax malarias in humans [66][67][68]. Murine malaria is exacerbated by a CTLA-4 blockade, which induces higher parasitemia than in controls [69][70][71].…”
Section: The Genomic Factors Associated With Vitamin D In Malariamentioning
confidence: 99%